KINERJA REPRODUKSI DENGAN INDUKSI OODEV DALAM VITELOGNESIS PADA REMATURASI INDUK IKAN PATIN (Pangasius hypophthalmus) DI DALAM WADAH BUDIDAYA - Agus Tinus (Fish Scientiae, 2019)
The objective of this research was to study the effect of Oodev as know as PMSGad gonad rematurity in infertile broodstock of P. hypophthalmus by Oodev Hormoneinjection. The treatments consisted of control 0 ml Oodev/kg fish weight (D), 0,3 mlOodev/kg fish weight (A). 0,5 ml Oodev/kg fish weight (B) and 0,ml Oodev/kg fishweight (C). with four replications of each. Fish weight at the beginning of experiment was 5 to 7 kg/individual. The result showed that Oodev had positive effect on eggmaturation. This was shown by the value of average of eggs diameter. The maximumsize of egg diameter for fish with hormone injection were larger than without injection. The best treatment was 0,5 ml Oodev/kg fish weight(B) and the largest than those of group C and A. It was concluded that injection of Oodev (PMSGad) is effective in promoting gonad maturation and oocyte development in the catfish.